Dukungan Penyuluhan dan Lingkungan Ekternal terhadap Adopsi Inovasi dan Keberlanjutan Usaha Pertanian Padi Organik - Gunawan Gunawan; Aida Vitayala S Hubeis; Anna Fatchiya; Djoko Susanto (Agriekonomika, 2019)
The implementation of organic rice farming requires farmers who have different behaviors from the knowledge, attitudes and skills of farming that has been built up so far. The purpose of this research was to analyze the agriculture extension support, analyze the external support, and analyze the factors that influence adoption of innovation and the sustainability of organic rice farming. Research locations in Bondowoso District and Banyuwangi District, East Java Province. The sample of this study amounted to 224 respondents from 670 populations of organic rice farmers. The research method used surveys to get quantitative data and deepened with qualitative data. Analysis techniques with descriptive analysis and Structural Equition Model. The results showed that agricultural extension support in the low category. The indicators of extension subject, capability of extension advisor and intensity of agricultural extension in the high category. The indicator  of variable external support such as policy support, farmers group support, and  information access in th high category. The level of  implementation  organic rice farming in the indicators of economy, social, and environment aspect was in the high category.  The factor that influence the adoption of innovation was agricultural extension support. The factors that influence the implementation of sustainability  of organic rice farming systems were (1) innovation adoption,  (2) agricultural extension support, and (3) external support.